Chemotherapy-induced acute kidney injury: epidemiology, pathophysiology, and therapeutic approaches - Lyrio, Rafaella Maria da Cunha; Rocha, Bruna Reis Araújo; Corrêa, Ana Luiza Rodrigues Mascarenhas; Mascarenhas, Maria Gabriela Santana; Santos, Felipe Luz; Maia, Rafael da Hora; Segundo, Lívia Benezath; de Almeida, Paulo André Abreu; Moreira, Clara Magalhães Oliveira; Sassi, Rafael Hennemann (Frontiers in Nephrology, 2024)
Despite significant advancements in oncology, conventional chemotherapy remains the primary treatment for diverse malignancies. Acute kidney injury (AKI) stands out as one of the most prevalent and severe adverse effects associated with these cytotoxic agents. While platinum compounds are well-known for their nephrotoxic potential, other drugs including antimetabolites, alkylating agents, and antitumor antibiotics are also associated. The onset of AKI poses substantial risks, including heightened morbidity and mortality rates, prolonged hospital stays, treatment interruptions, and the need for renal replacement therapy, all of which impede optimal patient care. Various proactive measures, such as aggressive hydration and diuresis, have been identified as potential strategies to mitigate AKI; however, preventing its occurrence during chemotherapy remains challenging. Additionally, several factors, including intravascular volume depletion, sepsis, exposure to other nephrotoxic agents, tumor lysis syndrome, and direct damage from cancer’s pathophysiology, frequently contribute to or exacerbate kidney injury. This article aims to comprehensively review the epidemiology, mechanisms of injury, diagnosis, treatment options, and prevention strategies for AKI induced by conventional chemotherapy.